Eksperimen Optimasi Kekerasan Paduan Kuningan dengan Metode Desain Faktorial 33 - Novira Dwi Rahma; Gunawan Madyono Putro; S. Sadi; Muhammad Shodiq Abdul Khanan (OPSI, 2019)
Brass material is widely used by SME industries in Indonesia including the gamelan industry, the pottery industry, and the handicraft industry. This research aims to improve the quality of brass material which is a combination of copper and nickel material. The ability of the manufacturing industry in Indonesia in processing mining raw materials with good quality is still low. There has not been a specific effort to improve quality through research and development. The long-term goal of this research is to build excellence in the material field in Indonesian industries. This advantage is very important for industries in Indonesia to compete globally.The method used is a 3 variable factorial design (temperature, temper time, cooling media) with each of 3 levels (33) to determine the most influential factors and improve product quality so that the highest level of product hardness. From the results of data processing obtained from the three factors that have a significant effect and settings that provide the greatest level of violence viz